2021
DOI: 10.1108/nfs-10-2021-0293
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and biotechnological foods: an experimental study on consumer’s behaviour

Abstract: Purpose New food technologies based on biotechnological organisms are increasingly becoming a cause for debate and conflicting discussions. This paper aims to investigate hypothetical consumer behaviour, and the willingness to pay (WtP), towards a specific type of genetically modified food in relation to particular indications on the label about the implementation of corporate social responsibility (CSR) initiatives by manufacturing companies. Design/methodology/approach For this purpose a choice experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…The findings illustrate that consumers' perception of CSR plays a vital role in consumer decisionmaking toward GMFs adoption. These results support preceding literature that suggests CSR is associated with consumer reaction toward GMFs (Pino et al, 2016;Boccia and Covino, 2021;Rabbanee et al, 2021). Prior research on consumer behavior toward GMFs mainly focused on the effects of one or a few rare factors separately Jiang and Zhang, 2021;McKenzie et al, 2021;Rabbanee et al, 2021;Levi, 2022;Sleboda and Lagerkvist, 2022), while in this study, important influential factors were studied together and the analysis of their effects simultaneously to determine priorities.…”
Section: Theoretical Implicationsupporting
confidence: 84%
See 1 more Smart Citation
“…The findings illustrate that consumers' perception of CSR plays a vital role in consumer decisionmaking toward GMFs adoption. These results support preceding literature that suggests CSR is associated with consumer reaction toward GMFs (Pino et al, 2016;Boccia and Covino, 2021;Rabbanee et al, 2021). Prior research on consumer behavior toward GMFs mainly focused on the effects of one or a few rare factors separately Jiang and Zhang, 2021;McKenzie et al, 2021;Rabbanee et al, 2021;Levi, 2022;Sleboda and Lagerkvist, 2022), while in this study, important influential factors were studied together and the analysis of their effects simultaneously to determine priorities.…”
Section: Theoretical Implicationsupporting
confidence: 84%
“…In this respect, other scholars (van der Wees and Moonen, 2011; Pino et al, 2016;Boccia and Covino, 2021) referred to CSR initiatives that have a powerful effect on consumer decisions. Furthermore, in many developing and developed countries, the emphasis on biotechnological foods has recently increased (Alphonce et al, 2020), which has led to the growth of social problems.…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…Therefore, it can be concluded that GM food producer CSR could play an important role in reducing such concerns [ 20 ]. However, research background on the impact of CSR on attitudes towards GM food is extremely limited [ 21 , 22 , 23 ]. Previous research studies have proved that CSR have a significant impact on user attitudes [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research studies have employed the well-established Theory of Planned Behavior [ 23 , 27 , 28 ] to study consumer attitudes towards such products. However, these studies rarely focused on consumer perception about GM food producer CSR [ 21 , 22 , 24 , 29 ]. More specifically, previous studies have never applied a three-dimensional model of CSR, which relies on social, economic, and environmental dimensions of responsibility to GM food consumption [ 14 , 20 , 22 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation